Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5194/hess-16-105-2012
|View full text |Cite
|
Sign up to set email alerts
|

Improving estimated soil moisture fields through assimilation of AMSR-E soil moisture retrievals with an ensemble Kalman filter and a mass conservation constraint

Abstract: Abstract. Model simulated soil moisture fields are often biased due to errors in input parameters and deficiencies in model physics. Satellite derived soil moisture estimates, if retrieved appropriately, represent the spatial mean of near surface soil moisture in a footprint area, and can be used to reduce bias of model estimates (at locations near the surface) through data assimilation techniques. While assimilating the retrievals can reduce bias, it can also destroy the mass balance enforced by the model gov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 43 publications
(68 reference statements)
0
30
0
Order By: Relevance
“…For example, most remote sensing soil moisture products reflect the water status of a very shallow top layer of the soil, whereas hydrologic models typically simulate the water storage of a deeper soil column. Appropriate DA approaches for assimilating derived satellite products (e.g., Li et al, 2012) can mitigate but not entirely avoid this limitation. Assimilation of satellite radiance (i.e., brightness temperature) observations may also help to mitigate the conceptual mapping issue and has shown to result in improved atmospheric and hydrologic predictions (e.g., Masahiro et al, 2008;DeChant and Moradkhani, 2011a).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…For example, most remote sensing soil moisture products reflect the water status of a very shallow top layer of the soil, whereas hydrologic models typically simulate the water storage of a deeper soil column. Appropriate DA approaches for assimilating derived satellite products (e.g., Li et al, 2012) can mitigate but not entirely avoid this limitation. Assimilation of satellite radiance (i.e., brightness temperature) observations may also help to mitigate the conceptual mapping issue and has shown to result in improved atmospheric and hydrologic predictions (e.g., Masahiro et al, 2008;DeChant and Moradkhani, 2011a).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Errors caused by parameter uncertainty can also be accounted for by using the augmented state vector technique in the EnKF-based assimilation algorithm. Li et al [35] assimilated the Advanced Microwave Scanning Radiometer-Earth Observing System (AMSR-E) SM retrievals into the Noah LSM and found that the SM fields are less biased if a mass conservation scheme is implemented. This did not result in the expected maximum minimization of the estimation error because the algorithm only updated states and not parameters in the EnKF, and because the retrievals were not downscaled prior to using them in the model [35].…”
Section: Introductionmentioning
confidence: 98%
“…Li et al [35] assimilated the Advanced Microwave Scanning Radiometer-Earth Observing System (AMSR-E) SM retrievals into the Noah LSM and found that the SM fields are less biased if a mass conservation scheme is implemented. This did not result in the expected maximum minimization of the estimation error because the algorithm only updated states and not parameters in the EnKF, and because the retrievals were not downscaled prior to using them in the model [35]. Kaheil et al [36] used support vector machines (SVM) combined with variogram analysis to downscale and assimilate SM observations from airborne imagery from a scale of 800 to 50 m. Extending SVM-based methodology to coarser scales of satellite observations may be difficult due to computational complexity and over-fitting the training data [37], further complicated during dynamic vegetation and heterogenous micrometeorological conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Microwaves only penetrate the top few centimeters, retrieving only the surface soil moisture rather than the root-zone soil moisture. Some efforts have been done to estimate the soil moisture profile from the surface values [17]- [19], but these studies often encountered several obstacles, including the hydraulic parameterization, initial moisture condition, and satellite measurement accuracy [8], [20]. Another issue of satellite data is the shorter temporal record, which limits its application on the soil moisture extremes/agricultural drought assessment [21].…”
Section: Introductionmentioning
confidence: 99%